Mengembangkan Kompetensi Guru Dalam Melaksanakan Evaluasi Pembelajaran Di Era Merdeka Belajar - Suttrisno, Suttrisno; Yulia, Nurul Mahruzah; Fithriyah, Dewi Niswatul (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2022)
One of the merdeka belajar (freedom of learning) concepts give teachers the freedom to make fun learning. Teachers must make plans, carry out, and evaluate their learning programs independently. Teacher becomes the determining factor for the success of the learing objectives. And to find out the success of the learningprogram we need to do an evaluation. Evaluation is an important activity, which is carried out to review the success of a program to determine a decision. Teachers must have competence to conduct evaluations. The objectives of this study include; 1) to understand the concept of evaluations. 2) to explain teacher competence in carring out evaluations. The method used in writing this journal is a literature review, where research data obtained from several literary theories are processed and analyzed and then described, so that the results are obtained that in the early stages, teachers must first understand the concept of evaluation, which emphasizes the definition, objectives , the function of the principle and type of evaluation, while the competence of teachers in evaluation activities includes competence in planning evaluation programs, designing evaluation programs, developing evaluation programs, implementing, and evaluating evaluation programs. The evaluation itself requires data processing, reporting and utilization of the evaluation results.